Understanding genetic diversity, spatial genetic structure, and mating system through microsatellite markers for the conservation and sustainable use of Acrocomia aculeata (Jacq.) Lodd. Ex Mart. - Coelho, Natália Helena Pesso; Tambarussi, Evandro Vagner [UNESP]; Aguiar, Bruna Ibanes; Roque, Rafael H.; Portela, Renan Marcelo; Braga, Rayssa Chaves; Sanson, Daniela; Silva, Richeliel A. R.; Ferraz, Elza Martins; Moreno, Maria Andréia; Kageyama, Paulo Y.; Gandara, Flávio Bertin (Springer Nature, 2018)
Acrocomia aculeata is a native palm distributed widely throughout Brazil that is used in a diverse array of products from the food industry to biodiesel oil production. This study uses nine microsatellite loci to assess the genetic diversity, spatial genetic structure (SGS), and mating system of A. aculeata. A total of 200 samples were collected from four populations (Fusquinha—FU, Padre Josimo—PJ, Gleba XV-GB, and Amparo—AM), in São Paulo State, Brazil. We also collected fruits from 20 randomly selected seed trees in the FU population to assess mating patterns, for a total of 246 genotyped embryos. We identified a total of 103 alleles and all loci were polymorphic. The average observed heterozygosity (Ho) ranged from 0.410 (AM) to 0.531 (FU) and expected heterozygosity (He) ranged from 0.547 (PJ) to 0.615 (GB). The average fixation index (F) ranged from 0.043 to 0.254 for FU and AM populations, respectively. The coancestry coefficient (θx y) was significant up to 38 m in PJ the population and 71 m in AM. Individual palm outcrossing rates were predominantly high (tm = 0.985) and the paternity correlation (rp(m) = 0.02) was significantly low, indicating a high probability of the occurrence of half-sibs. Compared to other palm species, the studied populations show high levels of genetic diversity. Our results confirm that A. aculeata is primarily allogamous, with no significant paternity correlation, and seeds should be harvested from at least 40 trees to ensure high levels of genetic diversity in seed collection programs.
Keywords: Brazilian Atlantic forest; Conservation genetics; Microsatellite markers; Population genetics; Tropical palm species